NPY/Y1 receptor‐mediated vasoconstrictory and proliferative effects in pulmonary hypertension. (August 2014) - Crnkovic, S; Egemnazarov, B; Jain, P; Seay, U; Gattinger, N; Marsh, L M; Bálint, Z; Kovacs, G; Ghanim, B; Klepetko, W; Schermuly, R T; Weissmann, N; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose Pulmonary arteries (PAs) are innervated, but little is known about the role of neuronal axis in pulmonary hypertension (PH). Here, we have examined the role of the neuropeptide Y (NPY) and its Y1 receptor in PH pathogenesis. Experimental Approach NPY was localized by immunofluorescence. Expression of NPY and Y1 receptor were determined by quantitative PCR. Cellular response to NPY stimulation was assessed by Western blotting, thymidine incorporation and calcium imaging. Wire myography and isolated perfused mouse lung were applied to study pulmonary vasoactive effects of NPY. Selective receptor antagonists were used to assess the contribution of receptor subtypes in mediating NPY effects. Key Results Samples from PH patients showed increased NPYergic innervation within the PA wall and higher Y1 receptor expression, compared with donors. However, NPY levels were unchanged in both PA and serum. In the chronic hypoxic mouse model, Y1 receptor were up‐regulated, while expression of both NPY and Y1 receptor was increased in the lungs of monocrotaline and SU5416‐hypoxia rats. On a functional level, NPY acutely increased intracellular calcium levels and enhanced vasoconstriction of lung vessels preconstricted with adrenaline. Furthermore, NPY stimulated proliferation of human pulmonary arterial smooth muscle cells and activated p38 and PKD pathways. Correspondingly, higher phosphorylation of PKD was observed in remodelled vessels from PH patients. The selective Y1 receptor antagonist, BIBO 3304, concentration‐dependently inhibited vasoconstrictive and proliferative effects of NPY. Conclusions and Implications NPY and Y1 receptor are possible mediators of both vasoconstriction and pulmonary vascular remodelling in PH.